A cascaded energy management optimization method of multimode power-split hybrid electric vehicles. (15th May 2020) - Geng, Wenran; Lou, Diming; Wang, Chen; Zhang, Tong
Abstract: A novel multimode power-split hybrid electric vehicle demonstrates significant advantages in energy conservation. The complicated structure and multiple operation modes, however, have brought significant challenges to energy management. The problems of operation mode selection, power allocation, and operating point selection need to be solved simultaneously. Traditionally, existing energy management strategies first have determined operation mode and then have solved power allocation and operating points. Moreover, traditional dynamic programming usually has not considered electric energy consumption and has deviated from the optimal solution. To solve these problems, a cascaded energy management strategy that integrates dynamic programming and equivalent consumption minimization strategy (DP + ECMS) is proposed. An iterative method is used to optimize the equivalence factor. A vehicle model based on actual control strategy is established and validated by test results. Then fuel economy simulations are conducted. Results showed that DP + ECMS could achieve 19.9% fuel economy improvement compared with the rule-based strategy for a new European driving cycle. In addition, simulation results of a Worldwide Harmonized Light-Duty Test Cycle demonstrated that DP + ECMS performed well in real road driving conditions. This study introduces a novel multimode power-split hybrid system and provides a global energy management optimization method. Graphical abstract: Image 10601 Highlights: A novel multimode power-split hybrid system is introduced. A vehicle model based on actual vehicle control strategy is developed and validated. Operation mode, power allocation, and operating points are optimized simultaneously. A cascaded optimization method that integrates DP with ECMS is adopted. An iterative method is used to optimize the equivalence factor.